Humic substances and plant abiotic stress adaptation - Luciano Pasqualoto Canellas; Rakiely Martins da Silva; Jader Galba Busato; Fábio Lopes Olivares (Chemical and Biological Technologies in Agriculture, 2024)
Abstract Background Traditional agriculture is on the front line of climate change, being most impacted by the increase in the intensity and frequency of extreme events, such as floods, drought and rising temperatures. Local ecological knowledge is a recognized keystone of successfully managed socioecological systems, but loss of soil fertility, water scarcity, incidence of diseases and decreased production due to climate change are linked to the greater vulnerability experienced by traditional farmers. Plant biostimulants are natural products used to stimulate nutrient uptake and efficiency by crops, increase tolerance to abiotic/biotic stress and improve quality without negative impacts on the environment if obtained from renewed sources. Humic substances are some of the most used plant biostimulants in agriculture and play a central role in plant adaptation. Materials and methods We reviewed and discussed a sample set of papers (n = 52) about humic substances to mitigate abiotic stress in crops using data basis from Web of Science (Clarivate Analytics), Scopus—IBM (International Business Machines Corporation), and Scielo (Scientific Electronic Library Online). Results The predominance of authors in the global south is notable, but it is not a coincidence, since this is where the effects of climate change will have the greatest impact. The mechanisms involved in the stress mitigation involve the activation of signaling factors, gene response induction, the accumulation of osmoprotective and anti-oxidant compounds, the induction of antioxidative metabolism, ion homeostasis, membrane transport and adjustment of hormonal balance. The intriguing question is: how can a complex mixture of molecules affect so many distinct effects on plants responsible for plant adaptation? Conclusions The complexity of humic substances challenges our knowledge method, but supramolecular chemistry may provide answers that enable us to broaden our understanding of the plant defense mechanisms modulated by these substances. Graphical Abstract